Effect of operating conditions on electroforced sedimentation of zinc oxide - Jami, Mohammed Saedi; Iwata , Masashi; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail (2011)
Electroforced sedimentation experiments under constant electric current density of zinc oxide suspended in aqueous media were carried out and comparison is made between the experimental results and model predictions. The basic differential equation based on the model is solved analytically by assuming that both an electro-osmotic pressure gradient Epg and a modified consolidation coefficient Ce of the material are constant. The solution can explain the time course of changes in a solid compressive pressure distribution. The predicted final moisture distribution of the material agreed with our experimental observations. The progress of electroforced sedeimentation can be represented by an average consolidation ratio Uc as in mechanical expression. The effect of current density on the settling behavior is also studied.